Survival benefit of lung transplantation compared with medical management and pulmonary rehabilitation for patients with end-stage COPD. Issue 2 (27th April 2020) - Timofte, Irina; Wijesinha, Marniker; Vesselinov, Roumen; Kim, June; Reed, Robert; Sanchez, Pablo G.; Ladikos, Nicholas; Pham, Si; Kon, Zachary; Rajagopal, Keshava; Scharf, Steven M.; Wise, Robert; et al.
Background: COPD patients account for a large proportion of lung transplants; lung transplantation survival benefit for COPD patients is not well established. Methods: We identified 4521 COPD patients in the United Network for Organ Sharing (UNOS) dataset transplanted from May 2005 to August 2016, and 604 patients assigned to receive pulmonary rehabilitation and medical management in the National Emphysema Treatment Trial (NETT). After trimming the populations for NETT eligibility criteria and data completeness, 1337 UNOS and 596 NETT patients remained. Kaplan–Meier estimates of transplant-free survival from transplantation for UNOS, and NETT randomisation, were compared between propensity score-matched UNOS (n=401) and NETT (n=262) patients. Results: In propensity-matched analyses, transplanted patients had better survival compared to medically managed patients in NETT (p=0.003). Stratifying on 6 min walk distance (6 MWD) and FEV1, UNOS patients with 6 MWD <1000 ft (∼300 m) or FEV1 <20% of predicted had better survival than NETT counterparts (median survival 5.0 years UNOS versus 3.4 years NETT; log-rank p<0.0001), while UNOS patients with 6 MWD ≥1000 ft (∼300 m) and FEV1 ≥20% had similar survival to NETT counterparts (median survival, 5.4 years UNOS versus 4.9 years NETT; log-rank p=0.73), interaction p=0.01. Conclusions: Overall survival is better for matched lung transplant patients compared with medical management alone. Patients who derive maximum benefit are those with 6 MWD <1000 ft (∼300 m) or FEV1 <20% of predicted, compared with pulmonary rehabilitation and medical management. Lung transplantation offers a survival benefit for COPD patients with 6MWD <1000 ft (∼300 m) or FEV1 <20% of predicted compared to pulmonary rehabilitation and medical therapy. 6MWD and FEV1 should be considered in the transplant patient selection process. http://bit.ly/2SlkTIo